Initial inflammatory response after the pulpotomy of rat molars with MTA or ferric sulfate - LOPES,Camila Soares (2019)
Abstract Purpose To compare, both qualitatively and quantitatively, the inflammatory cells, vascular density and IL-6 immunolabeled cells present in the pulp after pulpotomy with white MTA versus 15.5% ferric sulfate (FS). Methodology Forty-eight mandibular first molars from 24 Wistar rats were divided into MTA or FS groups and subdivided according to the period after pulpotomy procedure (24, 48 and 72 hours). Four teeth (sound and untreated) were used as controls. Histological sections were obtained and assessed through the descriptive analysis of morphological aspects of pulp tissue and the quantification of inflammatory cells, vascular density and interleukin-6 (IL-6) expression. Data were statistically analyzed (p<0.05). Results The number of inflammatory cells was similar in both groups, being predominantly localized at the cervical radicular third. In the MTA group, increased inflammation was observed at 48 hours. Vascular density was similar in both groups and over time, being predominant in the medium radicular third. No correlation was found between the number of inflammatory cells and the vascular density. Pulp tissue was more organized in MTA-treated teeth. In both groups, a weak to moderate IL-6 expression was detected in odontoblasts and inflammatory cells. Comparing both groups, there was a greater IL-6 expression in the cervical radicular third of teeth treated with MTA at 24 hours and in the medium and apical thirds at 72 hours, while in the FS group a greater IL-6 expression was found in the apical third at 24 hours. Conclusion The MTA group presented better histological features and greater IL-6 expression than the FS group. However, no difference was observed between the groups regarding the inflammatory status and vascularization, suggesting the usefulness of FS as a low-cost alternative to MTA.